An efficient time-domain method for the electromagnetic transient response of multiconductor transmission lines excited by an electromagnetic field. Issue 7 (3rd May 2021) - Gong, Yanfei; Chen, Xingtong
Abstract : An efficient time-domain method based on the waveform relaxation with transverse partitioning (WR-TP) techniques and the delay extraction passive compact circuit (DEPACT) macromodel is presented for evaluating the electromagnetic (EM) transient response of multiconductor transmission lines (MTLs) excited by an external EM field. Firstly, the equivalent distributed sources due to the tangential components of the electric field are introduced into the MTLs equations. Then, the TLs are divided into a cascaded of DEPACT subnetworks, where the telegrapher's equations of lossless TLs are decoupled by applying the WR-TP techniques. And the relaxation sources over the lossy TLs are updated by using the waveform scaling algorithm, which can completely avoid performing the numerical convolution. Finally, the equivalent circuit is established and the transient responses induced on the lines can be obtained by using the circuit simulation software PSCAD.